PARP3 affects the relative contribution of homologous recombination and nonhomologous end-joining pathways. Issue 9 (5th March 2014) - Beck, Carole; Boehler, Christian; Guirouilh Barbat, Josée; Bonnet, Marie-Elise; Illuzzi, Giuditta; Ronde, Philippe; Gauthier, Laurent R.; Magroun, Najat; Rajendran, Anbazhagan; Lopez, Bernard S.; Scully, Ralph; Boussin, François D.; et al.
Abstract: The repair of toxic double-strand breaks (DSB) is critical for the maintenance of genome integrity. The major mechanisms that cope with DSB are: homologous recombination (HR) and classical or alternative nonhomologous end joining (C-NHEJ versus A-EJ). Because these pathways compete for the repair of DSB, the choice of the appropriate repair pathway is pivotal. Among the mechanisms that influence this choice, deoxyribonucleic acid (DNA) end resection plays a critical role by driving cells to HR, while accurate C-NHEJ is suppressed. Furthermore, end resection promotes error-prone A-EJ. Increasing evidence define Poly(ADP-ribose) polymerase 3 (PARP3, also known as ARTD3) as an important player in cellular response to DSB. In this work, we reveal a specific feature of PARP3 that together with Ku80 limits DNA end resection and thereby helps in making the choice between HR and NHEJ pathways. PARP3 interacts with and PARylates Ku70/Ku80. The depletion of PARP3 impairs the recruitment of YFP-Ku80 to laser-induced DNA damage sites and induces an imbalance between BRCA1 and 53BP1. Both events result in compromised accurate C-NHEJ and a concomitant increase in DNA end resection. Nevertheless, HR is significantly reduced upon PARP3 silencing while the enhanced end resection causes mutagenic deletions during A-EJ. As a result, the absence of PARP3 confers hypersensitivity to anti-tumoral drugs generating DSB.